Implementing Differentiated Instruction in Emancipated Curriculum: Narrative Review - Susanti, Arik; Trisusana, Anis; Asrori, Asrori; Sueb , Sueb; Zuhri , Fauris (Technium Social Sciences Journal, 2024)
The paper aims to provide a detailed description of the implementation of differentiated instruction in an emancipated curriculum. The purpose of this review was to provide a comprehensive summary of the current literature on a specific topic. Implementing differentiated teaching can be analyzed from four perspectives: learning material, instructional process, assessment, and learning environment. Through the implementation of differentiated instruction, teachers can actively involve students in the process of teaching and learning, hence enhancing students’ academic performance. Therefore, diversified learning may accommodate the diverse needs, cognitive preferences, and abilities of each student in a classroom environment. This approach not only promotes equity but also enhances student engagement and achievement. Professional educators are recommended to employ differentiated instruction as a method to actively include pupils in the learning process.